Clinical response to peroral endoscopic myotomy in patients with idiopathic achalasia at a minimum follow-up of 2 years. Issue 6 (30th April 2015) - Werner, Yuki B; Costamagna, Guido; Swanström, Lee L; von Renteln, Daniel; Familiari, Pietro; Sharata, Ahmed M; Noder, Tania; Schachschal, Guido; Kersten, Jan F; Rösch, Thomas
Abstract : Background: The recently developed technique for peroral endoscopic myotomy (POEM) has been shown to be effective in several short-term studies. Longer term outcome data are largely non-existent. Objective: To systematically report clinical outcome with a minimum post-POEM follow-up of 2 years. Design: All patients treated consecutively by POEM for achalasia at three centres were retrospectively analysed, with a minimum follow-up of 2 years. The main outcome was the rate of POEM failures (Eckardt score >3) related to follow-up time. Results: Of 85 patients treated, five (5.9%) cases were excluded due to protocol violation or loss to follow-up; the remaining 80 patients (mean age 44.9 years, 54% men) were followed clinically for 29 months (range 24–41). Initial clinical response was observed in 77 cases (96.3%). Clinical recurrences (later failures) were seen in a further 14 cases (17.7%), accounting for a total failure rate of 21.5%. In a multivariate analysis, age and endoscopic reflux signs were independent predictors of treatment success. Of the 17 failures, eight were among the first 10 cases treated in the participating centres. Reflux-associated sequelae included one case of a severe reflux-associated stricture requiring dilatation, and two patients with minor transient Eckardt score elevations curable by proton pump inhibitor (PPI) treatment. Endoscopic signs of reflux oesophagitis, mostly Los Angeles grade A/B, were seen in 37.5% (37/72) at the 2-year control. Conclusions: In this multicentre retrospective analysis, a high initial success rate of POEM is followed by a mid-term recurrence rate of 18%. Reflux oesophagitis, albeit mild, is frequent and should probably be treated by regular low-dose PPI therapy. Trial registration number: NCT 01405417 (UKE study).